3(0.6+2n)+3.2=7.6

Simple and best practice solution for 3(0.6+2n)+3.2=7.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(0.6+2n)+3.2=7.6 equation:


Simplifying
3(0.6 + 2n) + 3.2 = 7.6
(0.6 * 3 + 2n * 3) + 3.2 = 7.6
(1.8 + 6n) + 3.2 = 7.6

Reorder the terms:
1.8 + 3.2 + 6n = 7.6

Combine like terms: 1.8 + 3.2 = 5
5 + 6n = 7.6

Solving
5 + 6n = 7.6

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 6n = 7.6 + -5

Combine like terms: 5 + -5 = 0
0 + 6n = 7.6 + -5
6n = 7.6 + -5

Combine like terms: 7.6 + -5 = 2.6
6n = 2.6

Divide each side by '6'.
n = 0.4333333333

Simplifying
n = 0.4333333333

See similar equations:

| 60-11=x | | 3x^2+4x-4.75=0 | | 9=6x-10 | | 4+3(b+4)=-5(2b-11) | | 4.3-1.4(y+7)=-9.7 | | 4w^4+16w^2+15= | | 2(a-8)=-22+2a | | x+22=37.5 | | 5=6x-10 | | 4=6x-10 | | 3x=12.4 | | 22-4d=38 | | -10x^2-11x-3=0 | | 8(1+7x)=8-5x | | 2(b+3)=18 | | 4x^2-9=-16x | | 9(x+4)-2(3x-1)=50 | | -20=5g | | 2(7+7x)=14-x | | 2(3n+6)=3(12-2n) | | 3(4+x)=2x-5 | | 3m-11.5=4.2 | | -11=v+13 | | 2.4(b-3)+3.8=-8.2 | | 7y=43 | | 1841.6728=2*232.2344+l | | 2.5p+5=20 | | y+9=24 | | 2b-8=30 | | -30=f-2 | | 3(5+4)-x=20 | | -4+-3x+x^2=0 |

Equations solver categories